Challenges of Women Entrepreneurs in India and the Emerging Dimensions: A Study - Prof. Sowmya C.S.; Janvhi Mishra (International Journal of Engineering and Management Research, 2019)
Indian society today has witnessed a surge of women entrepreneurship. There arises a need to examine the challenges of women entrepreneurs in greater depth. This study attempts to understand these challenges as well as explore the dimensions that emerge from these challenges. The study is based on exploratory qualitative study of 20 women entrepreneurs in India. The narratives reveal six major themes: Desire to create self- identity and derive satisfaction through entrepreneurship, doing what one loves to do, perceiving risk taking as an enjoyable experience, entrepreneurship as a medium to contribute to society, success speaks for itself and willing to learn, unlearn and relearn.